E-Learning implementation in Malaysian universities: The Universiti Teknologi Malaysia experience - Puteh, Marlia (2008)
This paper evaluates Malaysian universities response towards their assignment of producing knowledge workers that began in 1996, after the establishment of the Multimedia Super Corridor. The Malaysian government economic reform during the 1990s included high expectations about the role of Malaysian universities in the production of knowledge workers. The need for knowledge workers was seen by the universities as a signal to move towards creating graduates with a good grounding in Information technology. The educational revolution that took place in 1996 saw significant changes in the strategies applied by the university sectors. In particular, mission statements of Malaysian private and public universities began to include objectives designed to promote e-learning methodologies and multimedia skills. In their recent struggle towards becoming internationally ranked universities, instigated by the Times Higher Education Supplement rankings, Malaysian universities are further compelled to demonstrate their academic excellence via the technology. These institutions failing efforts in accomplishing their mission statements are publicly debated and becoming a peril against their core agenda. This paper examines how a case study university charts its route towards this direction through its implementation of electronic learning. Specifically, it examines faculty resistance and acceptance towards the use of technology in delivering teaching. Rogers technology adopter model emphasized that convincing reluctant users to use the technology is most challenging as these people made up 84% of the members in an organization venturing into innovative practice. A similar occurrence was observed in the case study university. Why have these people been reluctant? This paper also investigates the difficult experience by university management in dealing with technology laggards. A key conclusion of this research is that Malaysian universities need to evaluate its e-learning strategies if they aim for e-learning to be established and aspire for successful attempts towards the creation of the requisite knowledge workers that Malaysia needs.